Occupational Gender Segregation In Rural Urban Economy - Yunisvita Yunisvita; Nurlina Muhyiddin (Universitas Negeri Malang, 2020)
Occupational Segregation by gender is an improved labor market based on gender equality. This study uses an index-D to measure segregation that occurred in four rural areas categorized urban districts and counties Banyuasin Ogan Ilir South Sumatra Province. It was found that in all four regions of the occupation by gender still be integrated because the value of the index-D approaches 1. Meanwhile, based on the Pearson correlation coefficient is known that occupational segregation by gender has a significant relationship, very strong and negative direction with the percentage of women in the workforce and age, while the direction of the opposite relationship with the difference in the percentage of men and women who have a high school education and above.